Effect of maternal environment on yolk immunoreactive corticosterone and its influence on adrenocortical and behavioral activity in chicks of Greater Rhea (Rhea americana) - Della Costa, Natalia Soledad; Navarro, Joaquín Luis; Bernad, Lucía; Marín, Raúl Héctor; Martella, Mónica Beatriz (Elsevier, 2019)
Maternal corticosterone in avian eggs may modify offspring phenotype in order to increase survival in poor environments. In the Greater Rhea (Rhea americana), we previously found that yolk immunoreactive corticosterone is influenced by the quality of the maternal environment: eggs laid by females of the intensive rearing system (IRS), living in poor captive conditions, had higher yolk immunoreactive corticosterone than those produced by females of the semi-extensive rearing system (SRS), living in better conditions. Here, we evaluate if these different hormone levels are associated with the production of different phenotypes. We collected eggs from the IRS and SRS for hormonal quantification and artificial incubation. Then, half of the chicks selected from each environment were exposed to a capture and restraint protocol, and the rest remained undisturbed and were used as controls. In the IRS, we found that higher yolk immunoreactive corticosterone was associated with the production of chicks that had reduced hatchability, lower hatchling mass and higher baseline fecal glucocorticoid metabolites (FGM) than those produced by SRS females. Moreover, after capture and restraint, IRS chicks did not modify their FGM nor their behaviors compared to their controls, while SRS chicks increased their FGM and spent more time ambulating and less time pecking, compared to their controls. These results indicate that yolk immunoreactive corticosterone could modify offspring phenotype. Although future studies are needed to elucidate their implications for fitness, our results suggest that yolk corticosterone could be mediating an adaptive maternal effect that allows individuals to better cope with poor conditions.